VD_FINDINFO Jug / 2022 / 7 vom 28. April 2021 - VD Tribunal cantonal (2021)
CONSTATATION DES FAITS, FIXATION DE LA PEINE, EXPULSIONDROIT PÉNAL, TENTATIVEDROIT PÉNAL, MEURTRE | 22 ad 111 CP, 47 CP, 66a al. 2 CP, 10 CPP (CH)